Ngapak Language as Discourses of Javanese Socio-Cultural Construct - Antoni, Nur; Fadlilah, Sayyidatul (Komunitas, 2022)
Linguistic data often record cultural values and reflects the social dynamics of society based on cultural values. The purpose of this study is to analyze the discourse and speech of the Javanese Ngapak language which contains cultural values and the way that culture is constructed through discourse and speech language. The object of this study is discourse and the approach used is linguistic-sociological, or usually called sociolinguistics. The method used in this paper is a qualitative descriptive research method that produces descriptive data in the form of speech, writing, or observed behavior, using the listening and writing technique. The results of the study show that good culture, religious teachings, and a culture of sharing with others are found in the discourse and utterances of the Ngapak Javanese language. These cultures are constructed through the Ngapak Javanese language in a relaxed, serious, prayer and humorous atmosphere, showing the reality of the Ngapak-speaking community. This means that cultural values are found in discourse in the form of community conversations, texts and speech in various forms which are constructed through the Javanese Ngapak language to reflect reality.